The last major earthquakes along the Magallanes-Fagnano fault system recorded by disturbed trees (Tierra del Fuego, South America) - Pedrera, Antonio (2014)
Forests situated above active fault zones may record hillslope evolution, thus holding information about recent seismic events. Lenga trees (Nothofagus pumilio) extend across the Magallanes-Fagnano fault system (MFFS), the active transform boundary between the South American and Scotia plates. Coseismic surface ruptures along the fault scarp tilt trees located uphill. During the interseismic period, tree growth curves the trunks. Annual tree-rings from the study area show abrupt changes from concentric to asymmetric, allowing the timing of major historical earthquakes to be established. In this case, tree-ring analysis suggests rupture on the MFFS fault scarp in 1883±5 and 1941±10, coinciding with the February 1, 1879 (Modified Mercalli Scale, VI) and the December 17, 1949 (Ms 7.8) earthquakes in Tierra del Fuego. Our results provide evidence that this fault system was the source of these earthquakes, which has implications for seismic hazard in the region of study.